2007
DOI: 10.1352/1934-9556(2007)45[149:acmtcr]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Community Membership Through Community Rehabilitation Provider Services: Are We There Yet?

Abstract: Findings from an analysis of the characteristics and services of community rehabilitation providers (CRPs) in the early years of the 21st century are presented. Services provided by CRPs can be categorized along two dimensions: purpose (work, nonwork) and setting (facility-based, community). The number of individuals with disabilities present provides a third perspective for analysis. The majority of CRPs provided both work and nonwork services, and the majority of those that provide employment services offere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 2 publications
0
34
0
Order By: Relevance
“…In fiscal year (FY) 2003, only 26% of individuals with intellectual and developmental disabilities supported by community rehabilitation providers worked in integrated jobs (Metzel, Boeltzig, Butterworth, Sulewski, & Gilmore, 2007). At the same time, participation in sheltered or facility-based employment and nonwork services has grown steadily for this group (Mank, 2003;Winsor & Butterworth, 2008).…”
mentioning
confidence: 99%
“…In fiscal year (FY) 2003, only 26% of individuals with intellectual and developmental disabilities supported by community rehabilitation providers worked in integrated jobs (Metzel, Boeltzig, Butterworth, Sulewski, & Gilmore, 2007). At the same time, participation in sheltered or facility-based employment and nonwork services has grown steadily for this group (Mank, 2003;Winsor & Butterworth, 2008).…”
mentioning
confidence: 99%
“…Though controversial and though their effectiveness has long been questioned (Jiranek & Kirby, 1990;National Disability Rights Network, 2011), workcenter, sheltered workshop or similar arrangements remain prevalent in disability and employment programs across the U.S. (Butterworth et al, 2012;Metzel et al, 2007). By the middle of the 1990s, sheltered workshops with FLSA subminimum wage certificates had proliferated to the extent that there were nearly 6,000 certified work center-based employers in community rehabilitation programs, employing over 240,000 individuals (Whittaker, 2005).…”
Section: Work-center Arrangements and Section 503 New Rulesmentioning
confidence: 99%
“…By the middle of the 1990s, sheltered workshops with FLSA subminimum wage certificates had proliferated to the extent that there were nearly 6,000 certified work center-based employers in community rehabilitation programs, employing over 240,000 individuals (Whittaker, 2005). Metzel et al (2007) analyzed the service characteristics of community rehabilitation programs in 2002 and found that 70 percent of these programs offered both sheltered and integrated employment services. The same study found that an additional 18 percent of programs provided employment only in integrated settings and 12 percent provided only sheltered employment.…”
Section: Work-center Arrangements and Section 503 New Rulesmentioning
confidence: 99%
“…Further, these young adults and their families must often find an appropriate agency (i.e., vocational rehabilitation, one-stop career center, independent living center) even before they sufficiently understand the formal supports available [21] and/or the eligibility criteria [13,36]. Given these organizational and systemic barriers, many families, particularly African American and Latino low-income families know little about the transition process or how to gain access to transition work options within the adult service system [26,27]. Even families that can access the adult work system quickly discover that services are limited, have long waiting lists, and/or are not appropriate for various reasons (e.g., skills level, transportation) [17,43].…”
Section: And F Balcazar / Predicting Community Versus Facility-basedmentioning
confidence: 99%